Rail road tie preservative recovery and conversion to hydrocarbon fuels: a conceptual process design and economics. (10th June 2018) - Houston, Ross; Haber, Holly; Kim, Pyoungchung; Kim, Jae‐Woo; Lloyd, Jeff; Labbé, Nicole; Abdoulmoumine, Nourredine
Abstract: In the USA, over 21 million wood railroad ties are produced per year to replace approximately 20 million used ties that have provided primary service in railroad tracks over 40 years. Traditionally, used ties have been processed for energy recovery, typically as boiler fuel. However, recent US Environmental Protection Agency (US EPA) regulations and the low cost of natural gas is leading to preservative‐treated ties being used increasingly as landfill. This study evaluated the economic viability of a process that aims to recover the preservatives from used ties and subsequently convert the extracted wood ties to hydrocarbon fuels (gasoline and diesel blendstocks) using an integrated biorefinery concept. This techno‐economic analysis considered three plants, geographically spread across the USA to minimize transportation costs, with a capacity of 1769 dry tons per day based on a yearly available used railroad‐tie inventory estimated at 2.33 million tons. Under the baseline case scenario, the process produces 237 tons per day of recovered creosote and 69 293 and 74 922 gal per day of gasoline and diesel, respectively. The total capital investment for an n th plant is estimated at 380 million. The minimum fuel selling price (MFSP) is determined to be 2.52 per gasoline gallon equivalent (GGE) at a 10% required internal rate of return in 2016 US dollars, with a simple payback period of 9 years after tax and a market price of recovered creosote of 2.80/gal. The sensitivity analysis reveals that plant size, internal rate of return, and feedstock cost have the most impact on the MFSP. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd